Crossed Andreev reflection in superconducting junctions (2008)
In this work crossed Andreev reflection (CAR) and elastic cotunneling (EC) are studied for junctions (N1ISIN2), where N1 and N2 are normal metals, S is a high Tc superconductor and I is an insulator. This study is carried out based on the analytical solutions of Bogoliubov de Gennes equations for anisotropic superconductors. The influence of different pair potential symmetries on the CAR and crossed conductance is analyzed. We show that CAR and EC are higher in dx2-y2 symmetry than in s symmetry. In the case of normal electrodes without magnetization, EC is the predominantly process for dx2-y2 symmetry, while in s symmetry, both processes decay with the same amplitude.